Zespół Ushera – opis przypadku - Kwiecień, Sława; Sulak, Robert; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The aim of this study is to present a case of coincidence of sensorineural hearing loss with chronic recurrent bilateral cystoid macular oedema in a 32-year-old woman, who was admitted to the clinic for deterioration of visual acuity of four months’ duration. The patient gave a history of hearing loss for 29 years. Visual field examination disclosed peripheral ring scotoma. Electrophysiological examination was performed: pattern visual evoked response was within normal limits and electroretinogram displayed diminished both photopic and scotopic response. As ophthalmoscopy demonstrated no pigment in the fundus of the eye, the findings were consisted with diagnosis of retinitis pigmentosis sine pigmento. The presence of loss of hearing indicated the necessity of performing the genetic examination for Usher’s syndrome. In order to establish a final diagnosis of Usher’s syndrome genetic examination must be performed, but family history is relevant. Early investigation for Usher’s syndrome in children with sensorineural hearing impairment is of a great significance. The patient may develop symptoms of retinitis pigmentosa in second or even third decade of his life. The necessity of thorough investigation for detecting other systemic abnormalities should be emphasized. There is no effective treatment of this syndrome. A child with Usher’s syndrome requires a comprehensive care of different medical specialties. Psychological, educational and sociological attitude is also of a great importance in the child development.